DANAU-DANAU VOLKANIK DI DATARAN TINGGI DIENG: PEMANFAATAN DAN MASALAH LINGKUNGAN YANG DIHADAPI - Sudarmadji Sudarmadji; Hari Supriyono; Sri Lestari (Universitas Gadjah Mada, 2015)
Volcanic lakes in the Dieng Plateau are famous because of their uniqueness; they have been used for various purposes. The area of Dieng Plateau has changed. The present land use is manly for the area of potato-producing farmland. In the area erosion process caused sedimentation in the lake to occur rapidly, it reduced the volume of the lake and water pollution. On the other hand, Dieng Local communities have been using water of these lakes. This study aims to: 1)inventory of volcanic lakes and environmental impacts that occur; 2. assess the environmental degradation in the area Dieng volcanic lake; and 3. assess the wisdom of local communities in the utilization of the lake. In this research, there are four lakes, namely Telaga Warna and Pengilon (as one unit), Telaga Merdada and Telaga Cebong were studied. This research was conducted by survey method. Field observation and interview with respondents were conducted. Water samples were collected from the lakes, followed laboratory analysis. Results of this study indicate that each lake has different potentials and problems. Telaga Warna and Pengilon potential as a tourist attraction that can be developed further, Telaga Merdada already in critical condition as a result of sedimentation and reducing of water volume, while the Telaga Cebong has a better conditions as local awareness for the conservation of the lake.